Paradoxes of Poweshiek Skipperling (Oarisma poweshiek) (Lepidoptera: Hesperiidae): Abundance Patterns and Management of a Highly Imperiled Prairie Species. (19th January 2014) - Swengel, Ann B.; Swengel, Scott R.
Abstract : Although Oarisma poweshiek sometimes occurred in localized abundance, its known range is centered on the highly decimated northern tallgrass prairie of North America. To aid its conservation, we analyze surveys from 1988 to 1997 of populations no longer being found. While we recorded 2403 individuals at 20 sites, five sites had 87% of individuals, while 12 sites had only 2% of individuals. Most surveys during O. poweshiek flight had zero individuals recorded. In peak vegetative characteristics for O. poweshiek, fire management had the highest mean abundance but the lowest median abundance and lowest percent occurrence compared to idling and haying. Mean abundance was by far the lowest in the first year postfire compared to longer since fire. Median abundance and percent unit surveys where O. poweshiek was found indicated higher abundances the longer since fire. Although this skipper occasionally exhibited super-recoveries after fire, the median result in fire-managed occupied sites was zero. In a few years, abundance appeared synchronized across many sites, either low (1993, 1997) or high (1994-1995). It is only through a constant focus on avoiding the worst-case scenario that the rare best-case scenario of long-term population persistence appears possible for O. poweshiek .